2020
DOI: 10.1101/2020.04.05.026633
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ACE 2 Coding Variants: A Potential X-linked Risk Factor for COVID-19 Disease

Abstract: 24Viral genetic variants are widely known to influence disease progression among infected 25 humans. Given the recent and rapid emergence of pandemic SARS-CoV-2 infection, the cause of 26 COVID-19 disease, viral protein variants have attracted research interest. However, little has yet been 27 written about genetic risk factors among human hosts. Human genetic variation has proven to affect 28 disease progression and outcome for important diseases such as HIV infection and malaria infestation. 29The fact that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 35 publications
3
32
1
Order By: Relevance
“…Different ACE2 variants are reported that show sexspecific expression [30][31][32]. Since ACE2 is an X chromosome encoded gene, the presence of disease or risk variants in men will be more detrimental [31].…”
Section: Coronavirus Infection and Therapeutic Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different ACE2 variants are reported that show sexspecific expression [30][31][32]. Since ACE2 is an X chromosome encoded gene, the presence of disease or risk variants in men will be more detrimental [31].…”
Section: Coronavirus Infection and Therapeutic Targetsmentioning
confidence: 99%
“…Different ACE2 variants are reported that show sexspecific expression [30][31][32]. Since ACE2 is an X chromosome encoded gene, the presence of disease or risk variants in men will be more detrimental [31]. It is suggested that the missense ACE2 variants could influence binding with spike proteins and this, in turn, will affect the progression of COVID-19 [31].…”
Section: Coronavirus Infection and Therapeutic Targetsmentioning
confidence: 99%
“…Some of this response is known to be linked to variation in how the immune system responds to infection, with some individuals experiencing a hyperinflammatory 'cytokine storm', which in turn aggravates respiratory failures and increases mortality risk 32,33 . There may also be some variation among humans in initial susceptibility to infection, such that approaches examining variation in ACE2 tissue expression and gene sequences can offer insight into variation in human susceptibility to COVID-19 [34][35][36][37] . Similarly, we can use such an approach to compare sequence variation across species, and hence try to predict the likely interspecific variation in susceptibility to initial infection.…”
Section: Introductionmentioning
confidence: 99%
“…This ACE2 variant was absent from the East Asian population (13,784 exomes) and was significantly rarer in the Middle East and Africa (Table 1). This particular variant has been reported before, but its clinical relevance was persistently dismissed because the codon 720, being far from ACE2-Spike protein interface, does not appear to be an obvious candidate for ACE2 receptor binding to the S-protein of SARS-CoV-2 18,29 . However, we noted that N720D is located 4 amino acids proximal to the TMPRSS2 cleavage site (aa 697-716) as shown in Supplementary Fig.…”
Section: Ace2 N720d Receptor Variation and Structural Modelingmentioning
confidence: 98%